MEWUJUDKAN KEUNGGULAN MADRASAH - Mulyono, Mulyono (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2009)
Existence of madrasah in Indonesia since decade 1990-an really show existence which continue strength, either through quantitative and also qualitative is. Relevant of growth, there [is] two fundamental matter needing careful with is. First, amount of private sector madrasah much more big than country madrasah; Both, madrasah born, grow, and expand from and for society. Level of society participation in education of this madrasah express that madrasah is true base on strength at society (education based community). All the growth push Departmental functionary of Religion, functionary of Local government, all Islamic educationist and also moslem society progressively believe that excellence of education of madrasah can be improved. They also believe that pre-eminent education which on the market by madrasah will be able to be accepted by moslem parent from various social status and circle. To reach excellence of madrasah hence enableness effort and renewal of system education of madrasah require to be [done/conducted] continuous so that can face various challenge according to growth of epoch in globalization era and area autonomy. Challenge faced by education system cover problems of generalization, quality of, education efficiency and relevansi. Keyword: Excellence, Madrasah